2022
DOI: 10.1371/journal.pone.0271132
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hypokalemia and clinical prognosis in Patients with COVID-19 in Yangzhou, China

Abstract: Background Hypokalemia is a frequent electrolyte imbalance in patients with COVID-19. The aim of this study was to estimate the association between hypokalemia and clinical prognosis in patients with moderate COVID-19. Methods A single-center, retrospective, observational study was conducted on 81 non-ICU admitted patients with moderate COVID-19 according to the criteria issued by the Chinese Health Bureau in the Third People’s Hospital of Yangzhou (Northern Jiangsu People’s Hospital New District Branch) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Interestingly, hypokalemia has also been shown to be an indicator of a poorer prognosis and longer days of negative nucleic acid conversion. It is thought that this may be due to the fact that the virus interferes with ACE2, a key factor in the enzymatic cascades that maintain adequate levels of potassium in cells, causing the dysregulation of cellular physiological activity [51]. This disruption of cellular physiological systems also appears to cause the dysregulation of electrolyte homeostasis and pH imbalance [52].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, hypokalemia has also been shown to be an indicator of a poorer prognosis and longer days of negative nucleic acid conversion. It is thought that this may be due to the fact that the virus interferes with ACE2, a key factor in the enzymatic cascades that maintain adequate levels of potassium in cells, causing the dysregulation of cellular physiological activity [51]. This disruption of cellular physiological systems also appears to cause the dysregulation of electrolyte homeostasis and pH imbalance [52].…”
Section: Discussionmentioning
confidence: 99%
“…Electrolyte imbalance can be used as a marker of poor prognosis for COVID-19 [ 37 ]. Data from Jiangtao Yin et al showed patients with hypokalemia are more likely to have prolonged TNPT and days of hospitalization [ 38 ]. The serum potassium might affect body temperature and thus extended time in hospital for symptomatic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The study outcome was ascertained through the presence of diagnostic codes or laboratory data, based on clinical guidelines and previous studies [ 8 , 24 , 25 ]. International Classification of Diseases 10th Revision (ICD-10) code E87.6 was used to identify cases of hypokalemia from in- or outpatient data.…”
Section: Methodsmentioning
confidence: 99%